Gender analysis of farmers’ perception of improved haricot bean (Phaseolus vulgaris L.) varieties in the West Region of Cameroon - Siri, Bella Ngoh; Tchouamo, Isaac Roger; Nchanji, Eileen Bogweh (Journal Issues Limited, 2020)
The introduction of improved varieties of haricot bean has been viewed as a strategy to increase haricot bean production. Thus, recognising the perception of men and women of these varieties can contribute to increase production. The study sought to analyse farmers’ perception of improved haricot bean varieties in the West region of Cameroon. A mixed-method was used in collecting data from six sub-divisions in the West region to evaluate men and women farmers’ perception of improved varieties of haricot bean in 2019. Result reveals that farmer’s desirable attributes of improved haricot bean varieties qualities were related to the fact that it was high yielding, highly tasteful, had good grain quality and size, diseases and drought-tolerant as well as accepted in the market. On the other hand, farmers did, not like varieties that are difficult to harvest, susceptible to excess rains, late-maturing and have low market demands. Thus, varieties which are not resistant to biotic and abiotic stress with low market demand should undergo a product replacement strategy to meet the desired attributes of men and women farmers.